Analisis Pemilihan Warna Pada Industri Produk Kubah Putra Jamin Padangpanjang - Aryadi, Mirda (SPACEPRO: Product Design Jurnal, 2023)
AbstractIndustrial designs in the field of dome architecture have long-term potential to become sustainable projects. The choice of color is an element of art that cannot be separated from the architectural design of the dome wherever this product is applied. The research "Analysis of color selection in the Putra Jamin Padang Panjang dome product industry" aims to understand the ideal and long-lasting color selection for Enamel and decorative dome products accompanied by studies on the use of standard paint for car painting. The research method used is descriptive analysis with a qualitative approach. This research is expected to contribute to similar business actors to be able to improve work quality in terms of color selection and product durability, so as to have products that have aesthetic value and high selling value.Keywords: dome, color, enamel, decorative.